Correlations and path analysis for yield components in irrigated rice - Anibele Streck, Eduardo; Almeida Aguiar, Gabriel; Karling Facchinello, Paulo Henrique; Perin, Lais; Kuhn Krüger, Tuise; Martins de Magalhães Júnior, Ariano (Comunicata Scientiae, 2018)
Grain yield of irrigated rice is a complex character resulting from the expression and association of different components, which should be considered by the breeder for an efficient process of selection of new genotypes. In this sense, the objective is to highlight the phenotypic correlations and the direct and indirect associations of the main components related to crop yield via path analysis. The experiment was carried out in an experimental field of the Lowlands Station of Embrapa Clima Temperado using six genotypes of irrigated rice: the cultivars BRS Pampa, BRS IRGA 409, BRS 7 ‘Taim’, BRS Sinuelo CL, BRS Pampeira and AB 10101 CL. The agronomic characters evaluated were grain yield, days to flowering, panicle length, panicle mass, number of fertile spikelets, number of sterile spikelets, number of tillers per plant, number of panicles per square meter, and mass of one thousand grains. The number of fertile spikelets, number of panicles per square meter, panicle mass and mass of one thousand grains influenced grain yield, both through phenotypic correlation and direct effects. In addition, there was a high direct linear tendency of these variables towards yield. Panicle length and number of sterile spikelets showed a potential of use in the indirect selection for grain yield.